Preservation Of Betawi Ondel-Ondel Art As Betawi Traditional Art In Jakarta - Pradini, Gagih; Awaloedin, Dipa Teruna; Agustiani, Fitri; Wittsdy, Joy Hendrikh (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Tourism has become one of the largest industries in the world and is a major mainstay in generating foreign exchange in various countries. The number of international tourists continues to increase. One of the arts in the city of Jakarta is Ondel-Ondel which is the icon of the city. The art elements in Ondel Ondel also describe how the city is. Art that is always preserved and maintained by the community. The people of Jakarta already have an awareness of the importance of Ondel-Ondel as a tourist attraction that can be favoured The author examines Ondel-Ondel Betawi Art because it has its uniqueness compared to other arts, besides the potential of cultural arts that need to be preserved and known to tourists visiting Jakarta in particular. This research method uses a descriptive qualitative approach, which is research whose purpose is to provide an overview of a problem, symptoms, facts, events, and reality broadly and deeply that relies on data in the form of text.